MEDIAMENTOR: USER ACCEPTANCE OF AN INTERACTIVE MULTIMEDIA LEARNING TOOL WITH PEDAGOGICAL AGENT SUPPORT - Annamalai, Subashini; Chei , Shin Leng (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study presents the design, development, and user acceptance evaluation of MediaMentor, an interactive multimedia learning application supported by a pedagogical agent. Grounded in Mayer’s Multimedia Learning Theory and guided by user-centred design principles, MediaMentor delivers animated lessons, guided narration, formative quizzes, and game-based reinforcement to support undergraduate learners in understanding foundational multimedia concepts. The application was developed using multimedia tools and underwent expert review prior to user evaluation. A quantitative summative evaluation involving 34 undergraduate students was conducted using an instrument adapted from the Technology Acceptance Model (TAM) and the USE (Usefulness, Satisfaction, Ease of Use) framework. Descriptive analyses revealed high levels of perceived usefulness, ease of use, satisfaction, and overall acceptance. Students reported that MediaMentor improved conceptual understanding, was easy to navigate, and provided an enjoyable and engaging learning experience through its pedagogical agent and interactive features. The findings demonstrate that MediaMentor is an effective, user-friendly, and motivating digital learning tool that complements traditional instruction in multimedia education. The study underscores the potential of pedagogical-agent-supported, multimedia-rich applications to improve conceptual understanding and learner engagement in higher education.